O24 Which sexually transmitted infections do gay and bisexual men find most scary and why? a qualitative focus group study in four cities in england. (8th June 2017) - Reid, David; Datta, Jessica; Wayal, Sonali; Mercer, Cath; Hughes, Gwenda; Weatherburn, Peter
Abstract : Introduction: Men who have sex with men (MSM) are a priority for STI prevention interventions including the promotion of regular testing and condom use. Effective intervention design requires understanding of MSM's knowledge and fear of STIs, which may affect attitudes and behaviour related to risk, testing and treatment. Methods: We recruited a diverse sample of MSM in four English cities, through social networking sites and community organisations. 61 men attended eight focus group discussions. Topics included knowledge and attitudes towards 11 STIs. Discussions were audio recorded, transcribed and analysed thematically. Results: Participants demonstrated variable knowledge and awareness of STIs. No focus groups were unanimous in their ranking of fear of STIs, although HIV and HCV were considered the most 'scary' in all groups. Fear of syphilis and herpes was also considerable. Gonorrhoea was considered a 'rite of passage' and was not widely feared. Other infections showed no clear patterning within or between groups. Participants suggested a complex range of explanations for fear of particular STIs. Participants weighed up the scary and less scary attributes depending on the extent of their knowledge and experience, their prevalence among MSM, associated stigma, transmission mechanisms, contagiousness, symptoms, severity, and the availability, effectiveness and ease of use of vaccines, treatment and/or cure. Discussion: Participants expressed a range of nuanced fears and concerns related to individual STIs and STI testing and treatment. Understanding these fears, and how they might be mitigated, will help improve the impact of interventions promoting STI testing and treatment.